PHYTOCHEMICAL SCREENING OF LICHENS EXTRACT Usnea sp. ON PINES IN THE BARRIAN HILL FOREST, NORTH SUMATRA - Ashar Hasairin; Ahmad Shafwan S Pulungan; Adi Hartono (JBIO: jurnal biosains (the journal of biosciences), 2022)
Lichen is an organism that has a high level of biodiversity and contains secondary metabolites. This study aims to determine the secondary metabolites of lichen extract Usnea sp. on Pine. Qualitative descriptive research method. Preparation of Usnea sp. extract. carried out by maceration method using 96% ethanol (1:10) for 5 days. The results of the study based on the phytochemical screening of the ethanol extract of lichen Usnea sp. contains alkaloids, flavonoids, saponins and tannins and triterpenoids. The results of the phytochemical screening showed a positive (+) result indicated by a change in color or the formation of a precipitate or the formation of foam after adding reagents to the test extract. Meanwhile, a negative result (-) is indicated by the absence of a change in color or the formation of precipitate or the formation of foam after adding reagents to the test extract.